2014
DOI: 10.1016/j.pain.2014.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation in patients with painful diabetic neuropathy: A multicentre randomized clinical trial

Abstract: Painful diabetic neuropathy (PDN) is a peripheral neuropathic pain condition that is often difficult to relieve. Spinal cord stimulation (SCS) is a proven effective therapy for various types of mixed neuropathic conditions, yet effectiveness of SCS treatment for PDN is not well established. To our knowledge, ours is the first multicentre randomized controlled trial investigating the effectiveness of SCS in patients with PDN. Sixty patients with PDN in the lower extremities refractory to conventional medical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
186
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(201 citation statements)
references
References 26 publications
(42 reference statements)
2
186
0
1
Order By: Relevance
“…Systematic reviews, randomized controlled trials and several case series provide evidence for the long-term efficacy of spinal cord stimulation when combined with medical treatment compared with medical management in various pain neuropathies 132134 , and has been shown to offer sustained results at 24 months of treatment 135,136 . Two randomized trials in individuals with painful diabetic neuropathy reported greater reduction in pain and improvements in measures of quality of life compared with controls 137,138 . Current European guidelines provide a weak recommendation for spinal cord stimulation (combined with medical treatment) in, for example, diabetic neuropathic pain 118,119,139 .…”
Section: Managementmentioning
confidence: 99%
“…Systematic reviews, randomized controlled trials and several case series provide evidence for the long-term efficacy of spinal cord stimulation when combined with medical treatment compared with medical management in various pain neuropathies 132134 , and has been shown to offer sustained results at 24 months of treatment 135,136 . Two randomized trials in individuals with painful diabetic neuropathy reported greater reduction in pain and improvements in measures of quality of life compared with controls 137,138 . Current European guidelines provide a weak recommendation for spinal cord stimulation (combined with medical treatment) in, for example, diabetic neuropathic pain 118,119,139 .…”
Section: Managementmentioning
confidence: 99%
“…Spinal cord stimulation (SCS) is a therapy for chronic pain, in which epidurally implanted electrodes stimulate primary afferent (Aβ) collaterals in the dorsal columns. SCS has resulted in significant pain reduction in PDPN patients . Nevertheless, in about 40% of the patients, the treatment effect is not sufficient .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Thus, the legacy of the gate control theory is mostly in its application to treatment. In an early critique, Peter Nathan 26 wrote "Ideas need to be fruitful; they do not have to be right.…”
Section: Introductionmentioning
confidence: 99%